Value Preferences of Ukrainian Senior Grade Students in War Conditions: Common and Different in the Regional Dimension - Sokurianska, Liudmyla; Bieliaieva , Viktoriia (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2025)
The article analyzes the value preferences of Ukrainian high school students in the context of the Russian-Ukrainian war. The authors propose their own definitions of the concepts “value preferences” (a hierarchically structured system of an individual’s life priorities, that is, a system of existential values and value priorities across all spheres of activity — professional, civic, political, family and domestic, educational, leisure, etc.) and “Ukrainian political nation” (a community of citizens of the Ukrainian state of all nationalities, linguistic and religious preferences, united by shared values, political interests, patriotic attitudes, respect for the history and culture of Ukraine, its state symbols, and a willingness to defend the sovereignty and territorial integrity of their country). The article presents the results of the nationwide sociological study “High School Student – 2024: Life and Educational-Professional Plans of Ukrainian High School Students in Wartime,” conducted at the initiative of the Sociological Association of Ukraine by researchers of the Department of Sociology of the Educational and Scientific Institute of Sociology and Media Communications at V. N. Karazin Kharkiv National University during October–November 2024. The study examines Ukrainian high school students’ orientations toward terminal and instrumental values, their educational and professional plans after completing secondary education, assessments of the prestige and attractiveness of various professions, motivation for obtaining higher education, professional choice, civic identity, and related issues. The authors conclude that the high level of civic identity and the recorded unity of value preferences among Ukrainian high school students across different spheres of their life activity, combined with the absence of significant interregional differences in these indicators, provide grounds to speak about the active formation of the Ukrainian political nation at the mesosocial level of this process.